Student Youth Legal Consciousness: Formation Problems and Prospects - Mischenko, Elena V. (2021)
The Article Relevance. In order to build the state of law and civic society, it is necessary to increase legal education of all citizens of the state in the field of human rights and freedoms, forms and methods of their protection. It is especially important to involve young people in this process actively, instill in them the desire to know more about their rights and show more interest in the legal field. The aim of the study is a systematic analysis of the legal consciousness of young people and the forms of organization of legal education of young people. Research methods: as a research method, a questionnaire survey was used as a method of collecting primary information, which allows determining the level of development of the legal consciousness of students. Research results: the article analyzes the forms of organization of young people’s legal education; recommendations on the use of forms of organization of young people’s legal education are developed. The novelty and originality of the study lies in the fact that for the first time the legal activity of students was studied. The low awareness of students about the laws on the rights of youth and the youth environment was revealed. It is shown that the core in the formation of a young person’s social activity is ideological nature. It is revealed that students allocate informing, training, consulting and propagandizing forms of legal education of young people. It is shown that in higher educational institutions, legal education of young people is organized through training, informing and propagandizing forms through seminars, lectures, round tables, discussion clubs, mass media, printed publications, the Internet, social advertising. It is determined that for the organization of youth legal education one should take into account the wishes of the students: to develop programs of volunteerism, including the legal education of young people as activity; to develop a network of free youth agencies, in which young people can get all kinds of advice; regularly hold free legal aid. Insufficient legal literacy of students and unwillingness of the majority of students to participate in the solution of any social problems are revealed. It is shown that students demonstrate political passivity due to frustration and distraction of moral guidelines. Practical significance: The data obtained in this work can be used in legal psychology, jurisprudence, pedagogy, as well as for further theoretical development of this issue.